EXPLORING THE CAREGIVING EXPERIENCE OF LATINO AND NON-HISPANIC WHITE CAREGIVERS ACROSS FOUR AGE COHORTS. (11th November 2018) - Villa, V; Wallace, S
Abstract: There is growing evidence that caregivers who are members of ethnic minority populations and younger provide more care than their older non-Hispanic white counterparts. Utilizing data from the California Health Interview Survey (CHIS) 2009, we examine caregiving activities among Latinos and non-Hispanic whites in four age categories including 65+, 45 to 64, 26 to 44, and 18 to 25. Utilizing OLS and Logistic regression statistical techniques we first examine whether race/ethnicity and age predict caregiving activities including: relationship of caregiver to care recipient, number of hours a week provide care, how long caregiver has provided care, number of people caregiver provides care for, amount of money spent out of pocket for caregiving, live with care recipient, receive pay for caregiving, and utilize respite services. Next we examine the impact that the interaction of race/ethnicity and age have on caregiving activities with gender, income, and social resources held constant. The results of the analysis find that Latino caregivers ages 18 to 25 are more likely than their non-Hispanic white counter parts to live with the care recipient, provide care for more than 2 care recipients and provide care for more hours per week. Similarly, Latino caregivers ages 45 to 64 provide care for more hours per week and are less likely than other caregivers to use respite services. The implications of the analysis point to the need for LTC services that meet the needs of caregivers across the age spectrum, and create awareness of the supportive services that exist for caregivers.